Tai Ahoms and the stars three ritual texts to ward off danger - Terwiel, B. J.; Wichasin, Ranoo; Cornell University Southeast Asia Program (Ithaca, N.Y. Southeast Asia Program, Cornell University, 1992)
Study of three necromantic texts in Ahom, hybrid language with Tai base and Assamese admixture, used by Tai people living in Assam, India, since 13th century.
English, Thai, and Ahom (roman and Ahom scripts).
Includes bibliographical references (p. [162]-165).
Includes index.
Keywords: Ahom language -- Texts; Ahoms (Indic people) -- Rites and ceremonies; Religious literature, Indic -- India -- Assam